BRAZILIAN LITERATURE AND SELF-CARE IN ADOLESCENCE - Monteiro, Solange Aparecida de Souza [UNESP] (Fundacao Univ Tocantins, 2022)
Our objective was to understand self-care in adolescence, presented by the book Rale Brasileira: quem e e como vive by Jesse Souza. In the same way that we tried to talk about everyday life and the drama lived by the family of the social typology considered by the work as Brazilian rabble, a class present in Brazilian social thought that considers such a social class as a non-class, that is, individuals declared to be needy or dangerous. An in-depth study was carried out in chapter 8 The misery of the love of the poor. The teenagers Jane and Dina were identified in face of their life stories, seeking to reveal the family experiences, the use of the body, sexuality, erotic love and the encounters and disagreements of the teenager from the rabble. This theme motivated us to seek a dialogue with Foucauldian contributions regarding self-care, would Jane and Dina be exercising self-care?
Keywords: Adolescence; Case Study; Take Care of Yourself